Insomnia Symptoms and Cardiovascular Disease among Older American Indians: The Native Elder Care Study. (19th December 2011) - Sabanayagam, Charumathi; Shankar, Anoop; Buchwald, Dedra; Goins, R. Turner
Abstract : Background . Cardiovascular disease (CVD) is the leading cause of death among American Indians. It is not known if symptoms of insomnia are associated with CVD in this population. Methods . We examined 449 American Indians aged ≥55 years from the Native Elder Care Study. The main outcome-of-interest was self-reported CVD. Results . Short sleep duration, daytime sleepiness, and difficulty falling asleep were positively associated with CVD after adjusting for demographic, lifestyle, and clinical risk factors. Compared with a sleep duration of 7 h, the multivariable odds ratio (OR) (95% confidence interval [CI]) of CVD among those with sleep duration ≤5 h was 2.89 (1.17–7.16). Similarly, the multivariable OR (95% CI) of CVD was 4.45 (1.85–10.72) and 2.60 (1.25–5.42) for daytime sleepiness >2 h and difficulty falling asleep often/always. Conclusion . Symptoms of insomnia including short sleep duration, daytime sleepiness, and difficulty falling asleep are independently associated with CVD in American Indians aged ≥55 years.